(untitled) (Brazilian Geographical Journal, 2013)
Eateries are business franchises which predominantly deal is the sale of prepared food. The paper examines the spatial pattern of eateries in Ibadan North Local Government Area of Oyo-State. Also, the nature of patronage was examined and explained within the context of this research work. The Nearest Neighbour Analysis (NNA) was used to analyze the distribution of eateries within the study area and it was observed that the distribution of eateries within the local government area assumed a clustered pattern as against what was hypothetically stated. An Rn value of 0.38815 (P < 0.05) indicates a clustered pattern of distribution. Frequency tables and mean rank values were used to reveal the most important factor that determines the location of eateries in space and it was discovered that proximity to customers was the most important factor of location. The mean rank value for this factor was 6.79 being the closest to the maximum of 8. The result of the correlation analysis which was used to test for the relationship between the frequency of patronage of eateries and the distance of patrons form the eateries envisaged that there is a significant relationship between the frequency of patronage and the distance of patrons form the eateries. The R value of -0.251 (P < 0.05) shows that an inverse relationship exists between the two variables of interest. In addition to this, the chi-square value of 39.187 (P < 0.05) indicates that there is significant relationship between the frequency of patronage and the occupation of patrons. Also, the X2 value of 22.030 (P < 0.05) indicates that there is a significant association between marital status and the frequency of patronage.